2019
DOI: 10.3390/rs11070738
|View full text |Cite
|
Sign up to set email alerts
|

Improving Aboveground Biomass Estimation of Pinus densata Forests in Yunnan Using Landsat 8 Imagery by Incorporating Age Dummy Variable and Method Comparison

Abstract: Optical remote sensing data have been widely used for estimating forest aboveground biomass (AGB). However, the use of optical images is often restricted by the saturation of spectral reflectance for forests that have multilayered and complex canopy structures and high AGB values and by the effect of spectral reflectance from underlayer shrub, grass, and bare soil for young stands. This usually leads to overestimations and underestimations for smaller and larger values, respectively, and makes it very challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 87 publications
2
36
0
Order By: Relevance
“…The bands consisted of Band1-coastal aerosol, band2-blue (BLU), band3-green (GRN), band4-red (RED), band5-near infrared (NIR), band6-shortwave infrared 1 (SWIR1), and band7-shortwave infrared 2 (SWIR2). The 22 vegetation indices were consistent with those in the study by Ou et al [26], including normalized difference vegetation index (NDVI), simple ratio index (RVI), difference vegetation index (DVI), perpendicular vegetation index (PVI), two soil adjusted vegetation indices, brightness, greenness and temperature vegetation indices, atmospherically resistant vegetation index (ARVI), modified soil adjusted vegetation index (MSAVI), etc. In addition, a total of 224 grey-level co-occurrence matrix-based texture measures including mean, angular second moment, contrast, correlation, dissimilarity, entropy, homogeneity, and variance were derived using moving windows of 3 × 3, 5 × 5, 7 × 7 and 9 × 9 pixels, respectively.…”
Section: Collection and Preprocessing Of Landsat 8 Imagessupporting
confidence: 87%
See 3 more Smart Citations
“…The bands consisted of Band1-coastal aerosol, band2-blue (BLU), band3-green (GRN), band4-red (RED), band5-near infrared (NIR), band6-shortwave infrared 1 (SWIR1), and band7-shortwave infrared 2 (SWIR2). The 22 vegetation indices were consistent with those in the study by Ou et al [26], including normalized difference vegetation index (NDVI), simple ratio index (RVI), difference vegetation index (DVI), perpendicular vegetation index (PVI), two soil adjusted vegetation indices, brightness, greenness and temperature vegetation indices, atmospherically resistant vegetation index (ARVI), modified soil adjusted vegetation index (MSAVI), etc. In addition, a total of 224 grey-level co-occurrence matrix-based texture measures including mean, angular second moment, contrast, correlation, dissimilarity, entropy, homogeneity, and variance were derived using moving windows of 3 × 3, 5 × 5, 7 × 7 and 9 × 9 pixels, respectively.…”
Section: Collection and Preprocessing Of Landsat 8 Imagessupporting
confidence: 87%
“…The relative humidity is 70%, and the evaporation is 1671 mm. Dark brown forest soil and cold temperate coniferous forests are commonly found with dominant tree species of Abies, Pinus, Larix, and Picea [26].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The high FSV areas often have complex canopy structures, which may affect the reflectance values. A similar study by Ou et al [106] also found this was a common problem in the estimation of the FSV or biomass using multispectral remote sensing data. However, if the forest area with a low FSV and the forest area with a high FSV reach a certain ratio, the underestimation and overestimation problems of the RF will reach a certain balance.…”
Section: Discussionmentioning
confidence: 65%